Raising Students’ Awareness on Environmental Education Issues - Muh. Ichsan Ali; Amirullah Abduh; Ramlan Mahmud; Samirah Dunakhir (Indonesian Journal Of Educational Research and Review, 2023)
Environmental education is an important issue that is one of the topics at various levels of education throughout the world. The importance of environmental education as one of the best solution for preventing environmental damage.This study aims to analyze students’ awareness on environmental education issues in a pulic university. This case study research involve specific students who enroll in environmental education class. The total students who enroll in this study class is 47 students. The data collection instrument for this study is through google form questionnaires containing 18 items of awareness on environmental education issues. The instruments used in this study was pre-tested to ensure the credibility of the result of the study. The analysis approach of the questionnaire used Ms Excell tool for the percentage and then they are thematically placed in the results. The result of the study is that the research encounters two important themes: awareness on knowledge of environmental education and awareness of action on environmental education issues. The implication of the study is that there is a need to integrate both compulsory and voluntary programs from students from different levels of education aiming to raise students awareness on environmental education issues.